2006
DOI: 10.1111/j.1742-4658.2006.05135.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of eIF5A‐1 and eIF5A‐2 in human cancer cells

Abstract: Eukaryotic translation initiation factor 5A (eIF5A) is the only cellular protein that contains the unusual amino acid hypusine [Nε‐(4‐amino‐2‐hydroxybutyl)lysine]. Vertebrates carry two genes that encode two eIF5A isoforms, eIF5A‐1 and eIF5A‐2, which, in humans, are 84% identical. eIF5A‐1 mRNA (1.3 kb) and protein (18 kDa) are constitutively expressed in human cells. In contrast, expression of eIF5A‐2 mRNA (0.7–5.6 kb) and eIF5A‐2 protein (20 kDa) varies widely. Whereas eIF5A‐2 mRNA was demonstrable in most ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 49 publications
(44 reference statements)
3
96
0
5
Order By: Relevance
“…Hypusine is formed posttranslationally in a reaction catalyzed by DHS and DOHH and involving transfer of a 4-aminobutyl moiety from spermidine to Lys50 of eIF5A (15). The novelty of this modification in mammalian cells is reflected in the observation that only a single protein (eIF5A1/2) is detectable upon incubation of cells with 3 H-spermidine (25). eIF5A and its hypusinated form exhibit prolonged half-lives (≥24 hours) in many mammalian cells (40,41); strikingly, however, pulsechase studies revealed that eIF5A Hyp exhibits only approximately 6 hours of half-life in primary islets and islet-derived cell lines (present study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypusine is formed posttranslationally in a reaction catalyzed by DHS and DOHH and involving transfer of a 4-aminobutyl moiety from spermidine to Lys50 of eIF5A (15). The novelty of this modification in mammalian cells is reflected in the observation that only a single protein (eIF5A1/2) is detectable upon incubation of cells with 3 H-spermidine (25). eIF5A and its hypusinated form exhibit prolonged half-lives (≥24 hours) in many mammalian cells (40,41); strikingly, however, pulsechase studies revealed that eIF5A Hyp exhibits only approximately 6 hours of half-life in primary islets and islet-derived cell lines (present study).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian eIF5A exists as 2 isoforms, eIF5A1 and eIF5A2, which exhibit differing tissue distributions (25,26). As shown in Supplemental Figure 1 (supplemental material available online with this article; doi:10.1172/ JCI38924DS1), islets and islet-derived cell lines contain only the eIF5A1 isoform, which will henceforth be referred to simply as "eIF5A."…”
Section: Resultsmentioning
confidence: 99%
“…18 The eIF5A2 protein is also detectable in colorectal and ovarian cancer-derived cell lines. [18][19][20] Although the cancer-specific eif5a2 expression implies that eIF5A2 plays a role distinct from eIF5A1 in cancer cells, either human gene can restore the viability of a yeast eif5a mutant, suggesting functional similarity of the two human isoforms in eukaryotic cell survival. 17 The amino acid sequences of the human isoforms are conserved near the hypusination site, 17 suggesting that their function in cell survival might be linked to the hypusine modification.…”
Section: Introductionmentioning
confidence: 99%
“…K50A eIF5A mutant p3XFLAG-CMV-10.1 encoding for human eIF5A-1 was kindly provided by Myung Hee Park National Institute of Dental and Craniofacial Research "NIDCR" Bethesda, MD (Clement et al 2006). The mutant K50A was obtained in our lab using Quick Change Site-Directed Mutagenesis Kit (Stratagene).…”
Section: Rna Interferencementioning
confidence: 99%